Larval connectivity across temperature gradients and its potential effect on heat tolerance in coral populations. (30th May 2016) - Kleypas, Joan A.; Thompson, Diane M.; Castruccio, Frederic S.; Curchitser, Enrique N.; Pinsky, Malin; Watson, James R.
Abstract: Coral reefs are increasingly exposed to elevated temperatures that can cause coral bleaching and high levels of mortality of corals and associated organisms. The temperature threshold for coral bleaching depends on the acclimation and adaptation of corals to the local maximum temperature regime. However, because of larval dispersal, coral populations can receive larvae from corals that are adapted to very different temperature regimes. We combine an offline particle tracking routine with output from a high‐resolution physical oceanographic model to investigate whether connectivity of coral larvae between reefs of different thermal regimes could alter the thermal stress threshold of corals. Our results suggest that larval transport between reefs of widely varying temperatures is likely in the Coral Triangle and that accounting for this connectivity may be important in bleaching predictions. This has important implications in conservation planning, because connectivity may allow some reefs to have an inherited heat tolerance that is higher or lower than predicted based on local conditions alone.